Tanggung Jawab Produsen untuk Kebijakan Pengelolaan Sampah di Kota Tegal - Dinni Septianingrum; Kosuke Mizuno; Herdis Herdiansyah (Jurnal Penelitian Pendidikan IPA, 2023)
Solid waste management, which always ends in landfills, causes various environmental and socio-economic impacts. Tegal City also experiences overcapacity landfill conditions because the waste management model focuses on landfills. This study aims to identify existing waste management regulations and how EPR can become a policy framework to achieve waste management beyond landfills. The result explains that by regulation, the government has regulated the flow of solid waste management by prioritizing the 3R principles, starting from the transportation process, sorting at TPS/TPST, and even processing to become a product with economic value. However, in the end, all this waste still ends up in landfill. From the government's perspective, this is due to the need to integrate responsibilities between the government, society, and producers. Producer responsibility must be fully implemented in waste management. However, several regulations have yet to regulate the form of waste management that producers can carry out the responsibility of producers as specifically to be responsible for the product until it ends up as waste. In addition, this study illustrates that EPR as a policy framework for waste management can be applied in other cities, primarily if the government's point of view supports the division of responsibilities for waste management.